Regulating Long-Term Care Quality : An International Comparison - Mor, Vincent; Leone, Tiziana; Maresso, Anna (Cambridge : Cambridge University Press, 2014)
The number of elderly people relying on formal long-term care services is dramatically increasing year after year, and the challenge of ensuring the quality and financial stability of care provision is one faced by governments in both the developed and developing world. This edited book is the first to provide a comprehensive international survey of long-term care provision and regulation, built around a series of case studies from Europe, North America and Asia. The analytical framework allows the different approaches that countries have adopted to be compared side by side and readers are encouraged to consider which quality assurance approaches might best meet their own country's needs. Wider issues underpinning the need to regulate the quality of long-term care are also discussed. This timely book is a valuable resource for policymakers working in the health care sector, researchers and students taking graduate courses on health policy and management.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Long-term care of the sick; Cross-Cultural Comparison; Internationality